Investigation of functions characterizing the flow curves of cast magnesium alloy MgAl9Zn1 - A. Dziubinska; E. Siemionek; B. Koczurkiewicz; W. Presz (Metalurgija, 2024)
The article presents the results of testing the flow curves of cast magnesium alloy MgAl9Zn1. Experimental tests were carried out on a deformation dilatometer in a compression test of cylindrical specimens heated to 380 °C, 400 oC, 420 °C at strain rates of 0,1 s-1, 1 s-1, 10 s-1. The experimental curves were described by functions used in programs for simulating metal forming processes based on the finite element method. The Generalized Reduced Gradient optimization method (GRDM) implemented in Microsoft Excel was used to determine the function coefficients. Based on the results obtained, the best functions characterizing the flow curves were selected for use in describing the material models used in numerical simulations of cast magnesium alloy MgAl9Zn1.